C-3 benzoic acid derivatives of C-3 deoxybetulinic acid and deoxybetulin as HIV-1 maturation inhibitors. Issue 8 (15th April 2016) - Liu, Zheng; Swidorski, Jacob J.; Nowicka-Sans, Beata; Terry, Brian; Protack, Tricia; Lin, Zeyu; Samanta, Himadri; Zhang, Sharon; Li, Zhufang; Parker, Dawn D.; Rahematpura, Sandhya; Jenkins, Susan; et al.
Graphical abstract: Abstract: A series of C-3 phenyl- and heterocycle-substituted derivatives of C-3 deoxybetulinic acid and C-3 deoxybetulin was designed and synthesized as HIV-1 maturation inhibitors (MIs) and evaluated for their antiviral activity and cytotoxicity in cell culture. A 4-subsituted benzoic acid moiety was identified as an advantageous replacement for the 3′3′-dimethylsuccinate moiety present in previously disclosed MIs that illuminates new aspects of the topography of the pharmacophore. The new analogs exhibit excellent in vitro antiviral activity against wild-type (wt) virus and a lower serum shift when compared with the prototypical HIV-1 MI bevirimat (1, BVM), the first MI to be evaluated in clinical studies. Compound9a exhibits comparable cell culture potency toward wt virus as1 (WT EC50 = 16 nM for9a compared to 10 nM for1 ). However, the potency of9a is less affected by the presence of human serum, while the compound displays a similar pharmacokinetic profile in rats to1 . Hence9a, the 4-benzoic acid derivative of deoxybetulinic acid, represents a new starting point from which to explore the design of a 2nd generation MI.